2D resistivity model around the rupture area of the 2011 Tohoku-oki earthquake (Mw 9.0) - Hiroshi Ichihara; Takafumi Kasaya; Kiyoshi Baba; Tada-nori Goto; Makoto Yamano (Earth, Planets and Space, 2023)
Abstract The 2011 Tohoku-oki earthquake (Mw 9.0) was characterized by a huge fault slip on the shallowest part of the plate interface, where fault behavior had been believed to be aseismic. In this study, we modeled the two-dimensional resistivity distribution across the slip area based on ocean-bottom electromagnetic measurements to understand the physical properties around the plate interface controlling fault rupture processes. The optimal 2D resistivity model showed a conductive area around the shallowest plate interface where the huge coseismic slip was observed, whereas the deeper plate interface where the fault rupture was nucleated was relatively more resistive. The shallowest plate interface was interpreted to have a high pore seawater fraction, whereas the deeper interface was interpreted as a dry area. These findings are consistent with the hypothesis that aseismic frictional conditions changed to conditions enhancing fault rupture when the rupture propagated to the wet, clay-rich shallowest plate area. The optimal resistivity model also revealed a conductive area under the outer-rise area of the Pacific Plate. This finding supports the existence of a hydrated oceanic crust that supplied aqueous water to the subduction zone, including to the huge fault slip area. Graphical Abstract